Kajian Penggunaan Kriteria dan Indikator GSTC sebagai Instrumen Penilaian Pembangungan Pariwisata Berkelanjutan Berbasis Lingkungan - Irma Kharisma Hatibie; Srilian Laxmiwaty Dai; Anggraini M.S Lagalo (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2020)
The tourism sector is built based on development that prioritizes welfare, especially for people in rural areas. Not only as a sector that can provide an economic boost but at the same time providing a sense of security against concerns over the overexploitation of natural resources. Therefore, as part of the process in the management of a tourism destination, it requires an in-depth study of instruments that can assist tourism destination management in assessing the environmental resilience crisis. This instrument is needed to reduce environmental impacts, which are currently feared to damage the environment around the destination. One of the instruments used in this research is the criteria and indicators of the Global Sustainable Tourism Council (GSTC). The method of this research used a descriptive qualitative method, comparative analysis (implementation and indicators). The purpose of this research is to answer the challenges of environmental vulnerability issues in a destination using one of the GSTC criteria and indicators. The result of this research is Tunggul Arum tourism village does not fulfill the environmental-based on GSTC criteria and indicators.